ANTIOXIDANT ACTIVITY AND TOXICITY POLYSACCHARIDE EXTRACT FROM RED ALGAE Eucheuma cottonii AND Eucheuma spinosum - Muawanah Muawanah; Ahyar Ahmad; Hasnah Natsir (Marina Chimica Acta, 2016)
Red algae Eucheuma cottonii and Eucheuma spinosum which one alternative source of antioxidant and anticancer because contains polysaccharide compound. This research aims to isolate and examine the activity of antioxidant and toxicity polysaccharide extract from red algae Eucheuma cottonii and Eucheuma spinosum . The study was carried out by isolating the polysaccharide extract using water and methanol-ethanol precipitation. Antioxidant activity of crude extract was examined using 1,1-Difenil-2-pikrilhidrazil (DPPH) method, and toxicity test was carried out using Brine Shrimp Lethality Test (BSLT). The research results showed that the crude extract polysaccharide for Eucheuma cottonii and Eucheuma spinosum have strong antioxidant activity with IC50 value of 72,49 ppm and 75,98 ppm. The result of BSLT assay showed that the crude extract polysaccharide has a highest toxicity with LC50 value of 165,88 ppm and 337,21 ppm there are classified as toxic. The crude extract polysaccharide Eucheuma cottonii and Eucheuma spinosum has a potential to be developed as an alternative antioxidant and anticancer agent.